Intrinsic insight of energy-efficiency optimization for CO2 capture by amine-based solvent: effect of mass transfer and solvent regeneration. (July 2022) - Yuan, Bingling; Zhan, Guoxiong; Chen, Zhen; Li, Yuchen; Wang, Lidong; You, Changfu; Li, Junhua
Highlights: Performance of CO2 capture is investigated by orthogonal tests based on bench-scale system. Effect of flue gas flow is explored based on multiphase flow and mass transfer analysis. Energy-efficiency of CO2 capture is evaluated based on process simulation. Abstract: Here the energy-efficiency performance of CO2 capture is investigated based on the combination of bench-scale experiments and simulated calculation. A comprehensive evaluation is performed by L25 (5 6 ) orthogonal tests to analyze the effect of crucial operating conditions on CO2 capture. Experiments reveal desorption temperature and flue gas flow play a major role for CO2 capture efficiency. Rising flue gas flow could promote interfacial area, but decreases contact time, overally, net CO2 flow approximately determines the linear relationship of capture efficiency and absorption rate. With combination of Eulerian-Eulerian method with the population balance model, we predict the dynamics evolution process of dispersed bubble, in order to provide the detailed information of interphase contact area and multiphase flow for modelling complete mass transfer parameters. Meanwhile, rigorous process simulation is developed to analyze the energy consumption of carbon capture. Higher desorption temperature provides much leaner solvent, which is beneficial to CO2 absorption, but consumes greater energy penalty. Graphical abstract: Image, graphical abstract